Influence of PEG coating on the oral bioavailability of gold nanoparticles in rats - Ahmed Alalaiwe; Georgia Roberts; Paul Carpinone; John Munson; Stephen Roberts (Taylor & Francis Group, 2017)
Metallic nanoparticles can be produced in a variety of shapes, sizes, and surface chemistries, making them promising potential tools for drug delivery. Most studies to date have evaluated uptake of metallic nanoparticles from the GI tract with methods that are at best semi-quantitative. This study used the classical method of comparing blood concentration area under the curve (AUC) following intravenous and oral doses to determine the oral bioavailability of 1, 2 and 5 kDa PEG-coated 5 nm gold nanoparticles (AuNPs). Male rats were given a single intravenous dose (0.8 mg/kg) or oral (gavage) dose (8 mg/kg) of a PEG-coated AuNP, and the concentration of gold was measured in blood over time and in tissues (liver, spleen and kidney) at sacrifice. Blood concentrations following oral administration were inversely related to PEG size, and the AUC in blood was significantly greater for the 1 kDa PEG-coated AuNPs than particles coated with 2 or 5 kDa PEG. However, bioavailabilities of all of the particles were very low (< 0.1%). Concentrations in liver, spleen and kidney were similar after the intravenous doses, but kidney showed the highest concentrations after an oral dose. In addition to providing information on the bioavailability of AuNPs coated with PEG in the 1-5 kDa range, this study demonstrates the utility of applying the blood AUC approach to assess the quantitative oral bioavailability of metallic nanoparticles.